Changes in TRPC channel expression during postnatal development of cerebellar neurons. - Huang, W; Young, J; Glitsch, M (2007)
In the brain, classical (canonical) transient receptor potential (TRPC) channels are thought to be involved in different aspects of neuronal development. We investigated the developmental expression profile of TRPC channels in rat cerebellum during the first 6 weeks after birth. TRPC3 expression is significantly up-regulated whereas TRPC4 and TRPC6 expression are significantly down-regulated over this period of time. TRPC3 expression is mainly found on Purkinje cells and their dendrites, suggesting that the increase in TRPC3 expression reflects development of the dendritic tree of Purkinje cells. TRPC4 expression was restricted to granule and their precursor cells. TRPC6 expression is found on Purkinje cell bodies, on mature granule cells in the internal granule cell layer (but not their precursors) and interneurons in the molecular layer. The decrease in TRPC4 expression suggests that it is required for proper granule cell development whereas the decrease in TRPC6 expression is presumably correlated with interneuron development. Moreover, we demonstrate the presence of functional TRPC channels on Purkinje cell dendrites that are activated following stimulation of metabotropic glutamate receptors. Our results reveal cell-specific expression patterns for different TRPC proteins and suggest that developmental changes in TRPC protein expression may be required for proper postnatal cerebellar development.